Modelling systemic crises in interbank lending markets - Marttila, Iiro (My University, 2022)
Ever since the global financial crisis of late 2000s and early 2010s, there has been increased interest in the systemic risk and its measurement. Systemic risk is defined as the risk for severe financial crisis that spreads widely through the interconnected financial markets and has negative spillover effects on the broader economy. One trading network that causes this interconnectedness in the banking sector is the interbank lending market where banks can both lend and borrow short term loans which they use to manage their monetary reserves. For example, the distressed interbank lending markets further escalated the emerging systemic crisis during the late 2000s. Interbank lending markets and the monetary reserves of the individual banks are modelled with the system of coupled diffusion processes. In the model, banks lend money based on the differences in their monetary reserves and their lending preferences. Under specific assumptions, the total monetary reserves of the whole banking sector follow squared Bessel process where the dimension represents the total growth rate. The growth rate and the lending preference define whether the systemic crises exist in the banking system or not. In general, the banking sector benefits from the increased lending activities and higher growth rate as this decreases the probability of banks to go bankrupt. So called Mean field model ads some additional assumptions to the more general coupled diffusion model and these assumptions allow the model to be numerically simulated. When the interbank lending activity is high, then the reserves of the individual banks develop almost identically as the differences in the reserve levels diminish. However, this lending activity also causes adverse shocks to spread from one bank to all other banks. Therefore, if the lending activity in the markets is strong but the total growth rate is low, then the interbank lending activity actually increases the probability of severe systemic crisis. Further numerical analysis shows that it is better to increase the size of the banking system by adding new banks to the system rather than by increasing the sizes of the existing banks as the latter option increases the tail risks more than the former option. However, the Coupled banking model framework has many limitations that greatly drive these findings. Thus these limitations should be addressed in the future model development.

2000-Luvun lopulla ja 2010-luvun alussa taphtuneen globaalin finanssikriisin jälkeen systeemiriski ja sen mallintaminen ovat herättäneet erityistä kiinnostusta. Systeemiriski määritellään riskinä vakavalle finanssikriisille, joka leviää markkinoiden kautta toisiinsa kytkeytyneiden pankkien välityksellä ja aiheuttaa laskusuhdanteen finanssimarkkinoiden lisäksi myös reaalitaloudessa. Pankkien välisten lainamarkkinoiden kautta pankit hallinnoivat reservivivarojaan hyödyntäen lyhytaikaista anto- ja ottolainausta. Samalla kuitenkin nämä lainamarkkinat luovat pankkien välille riippuvuutta. Esimerkiksi juuri 2000-luvun lopun finanssikriisi kiihtyi ongelmiin joutuneiden pankkien välisten lainamarkkinoiden kautta. Pankkien välisiä lainamarkkinoita ja pankkien reservejä voidaan mallintaa hyödyntäen toisiinsa kytkeytyneitä stokastisia diffuusioprosesseja. Mallissa pankit lainaavat toisiltaan varoja perustuen pankkien reservitasojen välisiin eroihin ja pankkien omiin lainauspreferensseihin. Tiettyjen oletusten vallitessa pankkisysteemin kokonaisreservit seuraavat tällöin neliöityä Bessel prosessia, jonka dimensio puolestaan kuvaa pannkijärjestelmän kasvuvauhtia. Kasvuvauhti ja lainauspreferenssit yhdessä määrittävät sen, voiko pankkijärjestelmässä syntyä systeemikriisejä ollenkaan. Käytännössä pankit hyötyvät aktiivisista lainamarkkinoista ja korkeasta kasvuvauhdista, sillä nämä alentavat pankkien konkurssitodennäköisyyksiä. Niin sanotussa Mean field -mallissa tehdään yksinkertaistavia lisäoletuksia kytkeytyneeseen diffuusiomalliin, minkä ansiosta Mean field -mallia voidaan simuloida. Mallissa pankkien reservit kehittyvät lähes identtisesti silloin, kun pankkien väliset lainamarkkinat ovat aktiiviset, sillä aktiivinen lainaaminen tasoittaa eroja pankkien reservien välillä. Tällöin kuitenkin myös vakavat sokit leviävät pankkien välillä tehokkaasti. Jos pankkien väliset lainamarkkinat ovat aktiiviset ja pankkijärjestelmän kasvuvauhti on alhainen, aktiiviset lainamarkkinat itseasiassa lisäävät vakavan systeemikriisin todennäköisyyttä. Simuloimalla voidaan myös näyttää, että pankkijärjestelmän riskit pysyvät alhaisempina, mikäli järjestelmä kasvaa uusien pankkien kautta sen sijaan, että olemassa olevat pankit kasvattaisivat kokoaan. Kytkeytyneiden pankkien mallissa on kuitenkin useita rajoittavia oletuksia, jotka osaltaan johtavat esitettyihin tuloksiin. Mallia tulisikin kehittää niin, että näitä rajoitteita saadaan vähennettyä.
Keywords: Interbank lending, Monetary reserves, Systemic risk, Coupled banking model, Mean field model, Coupled diffusion process, Squared Bessel process